BOOK REVIEW: Sorin Nemeti, Irina Nemeti (ed.), “Studii asupra granițelor romane din Dacia. Castrul legionar de la Potaissa. I. Centuriae din praetentura sinistra”. Mega Publishing House, Cluj-Napoca, 279 p. - COCIŞ, Horațiu (Studia Universitatis Babeș-Bolyai Historia, 2018)
The monographic studies regarding the military installations of Dacia and their related issues have registered a severe decline in the past two decades, the main problem being, as F. Marcu remarked in the Foreword of the reviewed study, the lack of a coherent research direction. The legionary fort of Potaissa/Turda is one of the best examples from Romania/Roman Dacia of a not only continuously researched archaeological objective in the past 50 years, but, more importantly, of an archaeological site which, through successive research teams, assured a constant publishing of monographs and several associated studies. Moreover, they focused on various aspects of the military forma mentis of the soldiers of the legio V Macedonica, translated in archaeological areas, from architecture to daily life. The book presented in these pages belongs to the area of monographs, being the last but not least piece of work regarding the legionary fort of Potaissa, its focal point being an archaeological complex of military barracks-centuriae, from praetentura sinistra, investigated between 2012-2016 by a complex team of archaeologists led by Sorin Nemeti (Babeș-Bolyai University of Cluj-Napoca). The book was published under the auspices of the National Limes Commission, being part of a larger series of studies concerning the Roman frontiers of Dacia.